Characterization and expression analysis of MATEs in Cannabis sativa L. reveals genes involving in cannabinoid synthesis - Wang, Sifan; Cao, Xue; Meng, Xiangxiao; Aili, Maimaiti; Dou, Qin; Wang, Yan; Wahab, Atia Tul; Chen, Shilin; Sun, Wei; Wan, Huihua; Chen, Weiqiang (Frontiers in Plant Science, 2022)
The medicinal plant Cannabis sativa L. (C. sativa) accumulates plant cytotoxic but medicinally important cannabinoids in glandular trichomes and female flowers. Although the major biosynthetic pathway of cannabinoids has been revealed, their transportation mechanism is still unknown. Multidrug and toxic compound extrusion proteins (MATEs) can transport plant metabolites, ions and phytohormones intra and inter-cellularly. MATEs could have the potential to translocate cannabinoids or their synthetic intermediates to cellular compartment, thus protecting them from unwanted modifications and cytotoxicity. In this study, we performed a genome-wide identification and expression analysis of Cannabis sativa MATEs (CsMATEs) and revealed 42 CsMATEs that were classified phylogenetically into four conserved subfamilies. Forty-two CsMATEs were unevenly distributed on 10 chromosomes, with 50% CsMATEs were physically adjacent to at least one another CsMATEs and 83% CsMATEs localized on plasma membrane. Tandem duplication is the major evolutionary driving force for CsMATEs expansion. Real-time quantitative PCR revealed CsMATE23, CsMATE28 and CsMATE34 mainly expressed in flower, whereas CsMATE17 and CsMATE27 showed strong transcription in root. Light responsive cis-acting element was most abundant in promoters of CsMATE23, CsMATE28 and CsMATE34. Finally, the contents of cannabinoids and corresponding biosynthetic intermediates as well as expressions of CsMATE28 and CsMATE34 were determined under UV-B treatment, among which strong correlation was found. Our results indicates that CsMATEs might involve in biosynthesis of cannabinoids and has the potential to be used in heterologous production of cannabinoids.